Pengaruh Literasi Keuangan Islam, Sikap Terhadap Uang, dan Lingkungan Sosial Terhadap Perencanaan Keuangan Keluarga pada Pasangan Muda Muslim di Surabaya - Anindita, Nandini; Sukmaningrum, Puji Sucia; Rusmita, Sylva Alif (Airlangga Journal of Innovation Management, 2024)
Disciplined financial planning can create a more durable and financially stable marriage. However, many people still depend on fate, leading to financial planning being overlooked in daily life. Economic factors remain the second most common cause of divorce in Surabaya. Indonesia’s Sharia financial literacy index is only 8.93%, and only 6.3% of the population prepares for long-term financial goals. This study has the purpose of observing the modification theory of planned behavior with the variable Islamic financial literacy, attitude towards money, and social environment on family financial planning among young Muslim couples, especially in Surabaya. This research uses a quantitative approach used multiple linear regression analysis, utilizing IBM SPSS version 27 as the analytical tool. The subjects of this research are young Muslim couples in Surabaya, as younger generations often lack sufficient financial knowledge and tend to make poor financial decisions. The total sample consists of 75 respondents. The results show that Islamic financial literacy and social environment variables positively and significantly affect family financial planning. Meanwhile, the attitude towards money variable also shows an influence but is not statistically significant. These findings highlight the importance of improving Islamic financial literacy and leveraging the social environment to enhance family financial planning outcomes.